THE EFFECT OF EARLY MOBILIZATION ON PAIN LEVELS IN POST-LAPARATOMY SURGERY PATIENTS IN THE SURGICAL INPATIENT ROOM - Putra, Kurniawan; Widodo, Dyah; Sulastyawati, Sulastyawati; Marsaid, Marsaid (Indonesian Journal of Applied Health, 2025)
Complications that occur in post-laparotomy patients can include impaired tissue perfusion with thrombophlebitis, damage to skin integrity and protection problems in the form of pain. Postoperative pain occurs due to an inflammatory process that can stimulate pain receptors, which release chemicals in the form of histamine, bradychymine, prostaglandins, which cause pain in the patient. When suffering from pain, the patient will feel uncomfortable, if not treated immediately, the pain will have a negative impact on the lung, cardiovascular, digestive, endocrine and immune systems. This study aims to determine the effect of early mobilization on pain levels in patients after laparotomy surgery. The research design uses a pre-test and post-test control group design. The total research sample was 32 respondents using purposive sampling technique. The research instrument for measuring pain levels uses NRS (numerical rating scale). Pain response was measured before and after early mobilization. The statistical test used is the independent T-test. The results of the Independent T-test show a P-value of 0.000 < 0.005, so it can be concluded that there is an influence of early mobilization on the patient's pain level after laparotomy surgery. Based on the results of this research, early mobilization can help patients minimize pain so that the disease healing process will be shortened and it is hoped that hospitals will implement SOPs for early mobilization to reduce pain.